1996
DOI: 10.1097/00007890-199605270-00022
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Magnetic Beads Coated With Soluble Hla Class I or Class Ii Proteins in Antibody Screening and for Specificity Determination of Donor-Reactive Antibodies1

Abstract: An adequate method that will permit rapid specificity determination of donor reactive antibodies is urgently needed. Such a method could also be used for monitoring the presence of HLA antibodies in panel scanning. We here describe a method using magnetic beads coated with soluble HLA antigens that can be directly added to patient serum for efficient absorption of HLA antibodies. The entire procedure takes 45 min, and can therefore be easily adopted for use in acute crossmatching situations. Furthermore since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 7 publications
0
13
0
2
Order By: Relevance
“…However, our absorption experiments demonstrated that this assay was capable to detect antibodies directed against specific HLA-DR antigens and was not interfered by other molecules. Recently, antigen-specific immunotests using purified antigens coated in microtiter plate [30] or beads [31,32] were developed for the characterization of HLA class II antibodies in ELISA or flow cytometry technique, respectively. However, some epitopes could be destroyed by the isolation processes which might impair the binding of human alloantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, our absorption experiments demonstrated that this assay was capable to detect antibodies directed against specific HLA-DR antigens and was not interfered by other molecules. Recently, antigen-specific immunotests using purified antigens coated in microtiter plate [30] or beads [31,32] were developed for the characterization of HLA class II antibodies in ELISA or flow cytometry technique, respectively. However, some epitopes could be destroyed by the isolation processes which might impair the binding of human alloantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to other reliable techniques for HLA–Ab screening, i.e. ELISA [11]and fluorescence–activated cell sorting [12], which are not adversely affected by therapeutically applied LyAb, this new method is both cost effective and simple.…”
Section: Discussionmentioning
confidence: 99%
“…We described previously a new and quick method for the isolation of HLA class I and class II antigens using paramagnetic microbeads. 25 Microbeads coated with pooled HLA class I or II antigens were used for the removal of HLA antibodies from patient sera. The absorbed sera were retested for binding to LSECs.…”
Section: Methodsmentioning
confidence: 99%